2002
DOI: 10.1199/tab.0016
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular Waxes of Arabidopsis

Abstract: As in most terrestrial plants, the cuticle on Arabidopsis thaliana (L.) Heynh. forms a continuous lipid membrane over the apical epidermal cell walls of essentially all aerial plant organs. Epicuticular waxes form the outermost layer over this membrane and are visible on Arabidopsis inflorescence stem and silique surfaces as a bluish-white colored coating called glaucousness or waxy bloom. Intracuticular waxes are intermeshed within the cuticle membrane and not visible to the naked eye. Close examination of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
1
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 120 publications
(104 reference statements)
5
113
1
6
Order By: Relevance
“…In Arabidopsis, stem glossiness is generally indicative of altered epicuticular wax crystallization and is either due to general wax load reduction or to alteration of specific wax compounds (Jenks et al, 2002). Similar observations have been made in maize (Zea mays) and in rice (Oryza sativa) (Jenks et al, 2002;Islam et al, 2009).…”
Section: Tomato Ems Mutants For Studying Cuticle Composition and Propsupporting
confidence: 62%
“…In Arabidopsis, stem glossiness is generally indicative of altered epicuticular wax crystallization and is either due to general wax load reduction or to alteration of specific wax compounds (Jenks et al, 2002). Similar observations have been made in maize (Zea mays) and in rice (Oryza sativa) (Jenks et al, 2002;Islam et al, 2009).…”
Section: Tomato Ems Mutants For Studying Cuticle Composition and Propsupporting
confidence: 62%
“…As a result, alkane is assumed to be the in vivo substrate for the hydroxylation reactions in the wax biosynthetic pathway yielding secondary alcohols and ketones ( Fig. 1; Kolattukudy, 1996;Rashotte et al, 2001;Jenks et al, 2002). However, because these biosynthetic steps had not been confirmed to date, the alternative scenario could not be ruled out that acyl or aldehyde precursors may also be hydroxylated and the resulting hydroxyacids or hydroxyaldehydes transformed into secondary alcohols .…”
Section: Mah1 (Cyp96a15) Is a Midchain Alkane Hydroxylase Involved Inmentioning
confidence: 99%
“…Finally, MAH1 gene activity was highest in the actively growing parts of the inflorescence stems in the same regions where rapid cuticle formation occurs. Chemical analyses had shown that this is also the part of the plant surface where secondary alcohols and ketones accumulate most rapidly (Suh et al, 2005), whereas they are almost absent from the leaf wax (Jenks et al, 2002). Based on the perfect correlation between expression patterns and metabolite occurrence, it can be concluded that MAH1 functions mainly, or even exclusively, as a hydroxylase in the decarbonylation pathway of stem wax biosynthesis.…”
Section: Loss Of Mah1 Activity and Its Secondary Alcohol And Ketone Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The first barrier between plants and environmental stresses is the cuticle, which is composed of a lipophilic cutin polymer matrix and waxes (Holloway, 1982;Jeffree, 1996;Kunst et al, 2005;Nawrath, 2006). The cuticular waxes, which consist of very long chain fatty acids (VLCFAs; C20 to C34) and their derivatives, are embedded within and encase the cutin polymer matrix, a polyester framework composed of hydroxy fatty acids (C16 and C18) and glycerol monomers (Kolattukudy, 2001;Jenks et al, 2002;Nawrath, 2002;Heredia, 2003;Kunst and Samuels, 2003;Stark and Tian, 2006). The cuticle plays a role in limiting nonstomatal water loss and gas exchange, repelling lipophilic pathogenic spores and dust, providing mechanical strength and viscoelastic properties (Baker et al, 1982;Hoffmann-Benning and Kende, 1994;Riederer and Schreiber, 2001), preventing cell fusions (Lolle et al, 1998;Sieber et al, 2000), and protecting plants from environmental stresses (Schweizer et al, 1996).…”
mentioning
confidence: 99%